Effect of sandblasting time on the roughness of the metal cobalt-chromium (co-cr) during denture metal framework production - Kusdarjanti, Endang; R, Dwiyanti Feriana; Inayati, Eny (Folia Medica Indonesiana, 2017)
One of the stages of manufacture of denture metal framework that is sandblasting, ie cleaning the remnants of investment material after metal casting process and remnants of metal oxide on the surface. After fitting in the master model, then the metal framework dentures do sandblasting again until smooth before elektropolishing. The tools used are sandblaster, material Al2O3 (aluminum oxide) size of 250 lm. The time it takes about 1 minute, but the time of 1 minute when applied to student practicum D3 is still not clean and there are still remnants of planting material castings and metal oxide on the surface of the Co-Cr. Objective: To determine the effect of time on pembutan teeth iruan sandblasting the metal frame of the metal surface roughness Co-Cr. This study is experimental laboratories. A sample of tablet shape with a diameter of 7mm, 2mm thick metal. Number of samples 24 tablets were divided into 4 groups each group consisting of six tablet samples. Distribution of the sample group of the study are as follows; Group 1; Sandblasting metal surfaces with 250 µm Al2O3 time of 1 minute, Group 2; Sandblasting metal surfaces with Al2O3 250 ?m 2 minutes, Group 3; Sandblasting metal surfaces with Al2O3 250 µm 3 minutes, Group 4; the group did not do sandblasting. Data were analyzed with ANOVA statistical analysis of the lane with 0:05 significance level. If there is a significant difference between groups duiji with HSD test. There were significant differences in surface roughness Co-Cr metal between the control group without sprayed with the spray group at 1 minute, 2 minutes and 3 minutes. In conclusion, the surface of a metal frame that is not done sandblasting coarser than done sandblasting. The longer the time sandblasting increasingly produce a smooth surface of a metal frame. Sandblasting is perfectly need sufficient time is 2-3 minutes.